Association of Subgingival Microbiota Composition With Risk, Severity, and Outcome of Cryptogenic Ischemic Stroke in Young Adults - Manzoor, Muhammed; Zaric, Svetislav; Dong, Anbo; Leskelä, Jaakko; Pietiäinen, Milla; Könönen, Eija; Ylikotila, Pauli; Enzinger, Christian; Ropele, Stefan; Gattringer, Thomas; Eppinger, Sebastian; Sinisalo, Juha; et al. (Wiley-Blackwell, 2026)
Background
Oral and gut dysbiosis has been linked to stroke pathogenesis and its prognosis. However, the relationship between the subgingival microbiota and cryptogenic ischemic stroke (CIS) remains unclear. We compared the subgingival microbiota of patients with CIS and their age‐and sex‐matched stroke‐free controls to identify the specific microbiota associated with CIS, stroke symptom severity, and clinical outcome.
Methods
This multicenter, case–control study was conducted between 2013 and 2019 as part of a screening protocol for the SECRETO (Searching for Explanations for Cryptogenic Stroke in the Young: Revealing the Etiology, Triggers, and Outcome) study (NCT01934725). Stroke severity was assessed using the National Institutes of Health Stroke Scale score. After thorough clinical and radiographic oral examinations, subgingival samples were collected and analyzed using 16S rRNA gene sequencing.
Results
A total of 272 participants (134 patients and 138 controls) were included. There were no differences in the following clinical characteristics between patients and controls: diabetes, hypertension, smoking, alcohol use, abdominal obesity, physical activity, and chronic multiorgan disease. Beta diversity differed significantly between patients and controls (P<0.05). The abundance of Spirochaetota and Treponema was higher and Pseudomonadota, Veillonella, and Capnocytophaga were lower in patients than in controls (P<0.05). The abundance of T. denticola was associated with an increased risk of CIS (odds ratio [OR], 1.002 [95% CI, 1.000–1.003], P=0.023), and this association persisted after adjusting for relevant comorbidities and medications (OR, 1.002 [95% CI, 1.000–1.003], P=0.021).
Conclusions
The subgingival microbiota is associated with CIS, suggesting a possible link between oral health and stroke pathophysiology. Although causality cannot be proven, oral microbiota may be a modifiable treatment target for the prevention of CIS and improving its outcome.